Genomic landscape and efficacy of HER2-targeted therapy in patients with HER2-mutant non-small cell lung cancer - Han, Yanjie; Xiong, Yuanyuan; Lu, Tao; Chen, Rongrong; Liu, Yuan; Tang, Hui; Geng, Ruixuan; Wang, Yingyi (Frontiers in Oncology, 2023)
Background HER2-targeted therapy provides survival benefits to HER2-mutant non-small cell lung cancer (NSCLC). A better understanding of the clinical and genomic characterization of treatment-naïve HER2-positive NSCLC, as well as the efficacy of and resistance to HER2-targeted therapy in HER2-altered NSCLC, could promote further improvement of HER2 targeted therapy. Methods HER2-altered NSCLC patients was retrospectively included and their genomic profiles were performed by next-generation sequencing. The clinical outcomes included overall response rate, disease control rate and progression-free survival. Results Among 176 treatment-naïve patients with HER2 alterations, 64.8% harbored HER2 mutations with/without HER2 amplification, and 35.2% carried HER2 amplification only. Molecular characterization was correlated with tumor stage that late-stage NSCLC with HER2 oncogenic mutations showed a higher prevalence of TP53 mutations and a higher tumor mutation burden. However, this correlation was not found in patients with HER2 amplification only. Twenty-one patients with HER2 alterations treated with pyrotinib or afatinib were retrospectively enrolled. Pyrotinib yielded a longer median progression-free survival than afatinib (5.9 [95% CI, 3.8-13.0] vs. 4.0 months [95% CI, 1.9-6.3], P = 0.06) in these patients. Analysis of the genomic profiles before and after anti-HER2 targeted therapies identified de novo HER2 copy number gain and G518W mutation, as well as mutations involving DNA damage repair signaling, SWI–SNF complex, and epigenetic regulations as potential resistance mechanisms. Conclusion HER2-mutant NSCLC had different molecular features from HER2-amplified NSCLC, and its genomic profile was dependent of tumor stage. Pyrotinib had superior therapeutic effects than afatinib in HER2-altered NSCLC, although larger cohorts are warranted to validate it. HER2-dependent and -independent resistance mechanisms to afatinib and pyrotinib were unveiled.